Role-Playing to Foster 'Deep-Sea Exploration' Through Active and Virtual Learning: A Class-Design for Colombian Higher Education. Issue 3 (18th December 2020) - Sánchez, Juan Armando; Neira-Ramírez, Lorena; Rodríguez-Bermúdez, Adriana; Quattrini, Andrea
Deep-sea exploration is without doubt one of the most challenging-to-perform activities on Earth, as it faces natural limitations and it strongly relies on technological developments. Fortunately, advances in technology that are shaping the way we explore the deep sea can now be used to foster an innovative classroom environment. In this article we introduce a Deep-Sea Exploration graduate-level course with a foundation in active and virtual learning. Because virtual education is setting the pace in current times, here, we share the outline of this course with specific activities that can be used to engage and connect students from multidisciplinary backgrounds in contexts where barriers to perform deep-sea exploration are stronger. Students are expected to take three roles, researcher, entrepreneur, and explorer, to account for the intrinsic relationship between deep-sea scientists and other career practitioners. All roles prioritize collaborative work among students and motivate them to be creative, autonomous, and innovative. The course methodology exposes students to the deep-sea community through challenges such as grant proposal writing (Researcher), business idea innovation tanks (Entrepreneur), and novel discovery annotations on deep-sea exploration cruises streamed live via telepresence (Explorer). Beyond receiving information provided solely by lectures and readings, students in Deep-Sea Exploration use tools to build on their knowledge and to spot real-world opportunities for professional and sustainable community growth.